Radon and thoron concentrations and resulting dose in air of southeast Baghdad regions - Khalaf Rejah, Basim (International Journal of Engineering and Technology, 2018)
The levels of radon, thoron and their progeny concentrations in Al-Nayriya, Al-Musbah Street, Nawab Al-dhubat and Al-mashtel, as well as Canal Street in southeast Baghdad were studied by using The Twin Cup Dosimeter. A total of 15 samples selected from 5 regions (3 samples from each region) in Baghdad city have been placed in the dosimeters for 100 day. The average radon and thoron concentrations were found to be 45.47 and 43.15 Bq/m3 respectively. Their average progeny concentrations were found to be 4.91 and 1.16 mWL.The dose received by persons living in the studied areas is less than the internationally permissible limits, which were determined by the ICRP of 3-10 mSv /y.Â Â